Effects of Lumbriculus variegatus (Annelida, Oligochaete) bioturbation on zinc sediment chemistry and toxicity to the epi-benthic invertebrate Chironomus tepperi (Diptera: Chironomidae). (September 2016) - Colombo, Valentina; Pettigrove, Vincent J.; Hoffmann, Ary A.; Golding, Lisa A.
Abstract: Classical laboratory-based single-species sediment bioassays do not account for modifications to toxicity from bioturbation by benthic organisms which may impact predictions of contaminated sediment risk to biota in the field. This study aims to determine the effects of bioturbation on the toxicity of zinc measured in a standard laboratory bioassay conducted with chironomid larvae ( Chironomus tepperi ). The epi-benthic chironomid larvae were exposed to two different levels of sediment contamination (1600 and 1980 mg/kg of dry weight zinc) in the presence or absence of annelid worms ( Lumbriculus variegatus ) which are known to be tolerant to metal and to have a large impact on sediment properties through bioturbation. Chironomids had 5–6x higher survival in the presence of L. variegatus which shows that bioturbation had a beneficial effect on the chironomid larvae. Chemical analyses showed that bioturbation induced a flux of zinc from the pore water into the water column, thereby reducing the bioavailability of zinc in pore water to the chironomid larvae. This also suggested that pore water was the major exposure path for the chironomids to metals in sediment. During the study, annelid worms ( Oligochaetes ) produced a thin layer of faecal pellets at the sediment surface, a process known to: (i) create additional adsorption sites for zinc, thus reducing its availability, (ii) increase the microbial abundance that in turn could represent an additional food source for opportunistic C. tepperi larvae, and (iii) modify the microbial community's structure and alter the biogeochemical processes it governs thus indirectly impact zinc toxicity. This study represents a contribution in recognising bioturbating organisms as "ecological engineers" as they directly and indirectly influence metal bioavailability and impact other sediment-inhabiting species. This is significant and should be considered in risk assessment of zinc levels (and other metals) in contaminated sediment when extrapolating from laboratory studies to the field. Highlights: Bioturbation by Oligochaetes reduced zinc toxicity to chironomid larvae. Bioturbation caused the flux of zinc from the pore water into the water column to increase. Bioturbation needs to be considered in metal contaminated sediment risk assessments. Abstract : Ecological interactions such as bioturbation modify zinc sediment bioavailability and need to be considered in contaminated sediment risk assessments.